Purification and Characterization of Carbaryl Hydrolase from Blastobacter sp. Strain M501 - Hayatsu, Masahito (1993)
A bacterium capable of hydrolyzing carbaryl (1-naphthyl-N-methylcarbamate) was isolated from a soil enrichment. This bacterium was characterized taxonomically as a Blastobacter sp. and designated strain M501. A carbaryl hydrolase present in this strain was purified to homogeneity by protamine sulfate treatment, ammonium sulfate precipitation, and hydrophobic, anion-exchange, gel filtration, and hydroxylapatite chromatographies. The native enzyme had a molecular mass of 166,000 Da and was composed of two subunits with molecular masses of 84,000 Da. The optimum pH and temperature of the enzyme activity were 9.0 and 45°C, respectively. The enzyme was not stable at temperatures above 40°C. The purified enzyme hydrolyzed seven N-methylcarbamate insecticides and also exhibited activity against 1-naphthyl acetate and 4-nitrophenyl acetate.